FlaxLic supplementation improves growth performance of Angus bulls - A.C. Pesta; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2010)
Nutrition can affect bull fertility. Omega-3 fatty acids such as α linolenic, eicosapentaenoic, and docosahexaenoic acids can affect motility and morphology of sperm. Flaxseed is an excellent source of α linolenic acid and has been shown to increase tissue concentrations of both α linolenic acid and eicosapentaenoic acid, which are involved in synthesis of important reproductive hormones. Flax can be difficult to transport, process, and store, but the FlaxLic block (New Generation Feeds, Belle Fourche, SD) is stable and easy to handle, contains high levels of omega-3 fatty acids, and may be a useful supplement for developing beef bulls. In a previous study at Kansas State University, feeding FlaxLic blocks to developing bulls for 61 days prior to breeding soundness examinations increased rate of gain and percentages of motile and normal sperm. The FlaxLic block is a high-density, low-moisture product that resists heat and humidity. Blocks of this type typically are made with molasses. One of our study objectives was to determine whether corn steep liquor, when combined with molasses and subjected to high process temperatures (248°F to 284°F), could partially substitute for molasses with no significant change in block integrity or animal performance.
Keywords: Cattlemen& #x27; s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen& #x27; s Day; Beef; FlaxLic; Growth; Performance